THE IMAGE OF THE ETHNOSES IN THE WORLD VIEW OF THE SAKHA PEOPLE - Borisova, Izabella (Revista Inclusiones, 2020)
The article deals with the research in the field of interethnic relations. Reasoning and issue statement are stipulated by the poor study of interethnic relations within the country in the context of today’s Russia. The purpose of the article is to present the study of the historical basis and generalization of the current state of interethnic relations in Yakutia. The data may be of use to a wide range of readers interested in obtaining information on the deep interethnic processes occurring in the national state in the context of federal state consolidation. The study can fill in missing and relatively tabooed knowledge in the field of interethnic relations within a particular region, both theoretically and in practice. The article presents the results, obtained and elaborated by the author in the associative dictionary of the Yakut language (1220 respondents) and with the help of the method of quality attribution (450 respondents) (access mode: http://adictsakha.nsu.ru/corpora/corp). During the analysis of the legends on the relations of the peoples of Yakutia and the results of the associative experiment and the survey, it was concluded that interethnic relations are based on the available ethnic stereotypes and personal experience of the respondents. Respondents’ answers are applicable for creating and developing a policy of consolidation and tolerance in order to avoid ethnic conflicts and tensions in multinational Russia.